2021
DOI: 10.1039/d1ra05451a
|View full text |Cite
|
Sign up to set email alerts
|

X-ray excited luminescence spectroscopy and imaging with NaGdF4:Eu and Tb

Abstract: We synthesized and characterized Eu and Tb doped NaGdF4 nanophosphors which generate visible light when excited by a focused X-ray beam. High resolution images were acquired through tissue by measuring light intensity vs. X-ray beam position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…For the separated Gd 2 O 2 S:Eu nanoparticles (Figure 4c), we found a yield of ~13,400 photons/MeV, which corresponds to ~22% of the luminescence intensity of commercial Gd 2 O 2 S:Eu particles measured under the same conditions. Compared with previously reported synthesized particles, we found a yield of ~600 photons/MeV for the silica-coated 60 nm NaGdF 4 :Eu [8] and ~2400 photons/MeV and ~24,000 photons/MeV for ~60 nm Gd 2 O 2 S:Eu nanoparticles, synthesized with and without 7.5% NaF in the core, respectively [7].…”
Section: Nanoparticles Separation From a Polydispersed MIX Of Commerc...contrasting
confidence: 66%
See 1 more Smart Citation
“…For the separated Gd 2 O 2 S:Eu nanoparticles (Figure 4c), we found a yield of ~13,400 photons/MeV, which corresponds to ~22% of the luminescence intensity of commercial Gd 2 O 2 S:Eu particles measured under the same conditions. Compared with previously reported synthesized particles, we found a yield of ~600 photons/MeV for the silica-coated 60 nm NaGdF 4 :Eu [8] and ~2400 photons/MeV and ~24,000 photons/MeV for ~60 nm Gd 2 O 2 S:Eu nanoparticles, synthesized with and without 7.5% NaF in the core, respectively [7].…”
Section: Nanoparticles Separation From a Polydispersed MIX Of Commerc...contrasting
confidence: 66%
“…Unfortunately, most commercially available bright X-ray scintillators are micron-sized phosphors, which are inappropriate for many biological applications [5,6]. Our group and others are making efforts to synthesize and control the size of bright phosphor particles in nano scale [7][8][9][10]. For example, both conventional and non-conventional methods have been explored in the synthesis of nanomaterials doped with lanthanides for development of luminescent materials.…”
Section: Introduction and Theorymentioning
confidence: 99%
“…A key point of the "pre-crystallised nanoparticles route" is the processing of the fluoride nanoparticle suspensions. Some authors reported the preparation of NaGdF 4 nanoparticle suspensions [34][35][36][37]. In 2004, Mech et al [38] stated for the first time the preparation via hydrothermal synthesis of Eu 3+ -doped NaGdF 4 and KGdF 4 nanoparticles [38,39].…”
Section: Introductionmentioning
confidence: 99%